2016
DOI: 10.1042/bsr20160033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of human ABHD2 as TAG lipase and ester hydrolase

Abstract: Alterations in lipid metabolism have been progressively documented as a characteristic property of cancer cells. Though, human ABHD2 gene was found to be highly expressed in breast and lung cancers, its biochemical functionality is yet uncharacterized. In the present study we report, human ABHD2 as triacylglycerol (TAG) lipase along with ester hydrolysing capacity. Sequence analysis of ABHD2 revealed the presence of conserved motifs G205XS207XG209 and H120XXXXD125. Phylogenetic analysis showed homology to know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…In agreement with our conclusions, a number of studies have indicated that early onset fibrosis is significantly reduced after weight loss in obese subjects50. Abhd2 has been characterized as triacylglycerol (TAG) lipase and ester hydrolase51. Disruption of Abhd2 in mice leads to a decrease in alveolar type II cells in the lung and accumulation of macrophages in the lungs52.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our conclusions, a number of studies have indicated that early onset fibrosis is significantly reduced after weight loss in obese subjects50. Abhd2 has been characterized as triacylglycerol (TAG) lipase and ester hydrolase51. Disruption of Abhd2 in mice leads to a decrease in alveolar type II cells in the lung and accumulation of macrophages in the lungs52.…”
Section: Discussionsupporting
confidence: 91%
“…The data regarding the number of exons were obtained from BioGPS, and the data regarding the relatively high expression in normal human tissues were primarily obtained from the BioGPS portal and the reported references. protein name molecular weight (kDa) aliases gene location in humans number of exons relatively high expression in normal human tissues (BioGPS) related function or role in disease ABHD1 45 LABH1 2p23.3 9 testis, sperm saphenous related to oxidative stress in mouse and rat models [ 29 32 ]; expression downregulation is driven by hepatic steatosis and insulin resistance induced by Notch signalling [ 33 ] ABHD2 48 HS1–2, LABH2, PHPS1–2 15q26.1 16 prostate, lung, NK cells, whole blood a glyceridase and ester hydrolase cleaving 2AG and leading to sperm hyperactivation in a progesterone-dependent manner [ 34 36 ]; an androgen-regulated gene promoting prostate cancer growth and resistance to chemotherapy [ 37 ]; essential for the reproduction of HBV [ 38 , 39 ]; involved in calcium transfer from the endoplasmic reticulum to mitochondria [ 40 ] and chronic obstructive pulmonary disease (COPD) in a Chinese Han population [ 41 ]; associated with anoikis resistance in ovarian cancer [ 7 ] and possibly associated with tumorigenesis in hepatocytes, stomach cells and colon cells [ 42 , 43 ] ABHD3 46 LABH3 18q11.2 12 colon, small intestine, whole blood a brain serine hydrolase related to the activation of the endocannabinoid system [ 44 ]; a lipase playing the role of...…”
Section: Research Progress Related To the Abhd Family Membersmentioning
confidence: 99%
“…The results showed that, in the ABHD protein family, ABHD2, ABHD3, ABHD4, ABHD5, ABHD6, ABHD12 and ABHD16 participated in the metabolism of glycerine esters or phospholipids. ABHD2 is a new triglyceride lipase with an ester hydrolysing capacity [ 34 ]. In addition, ABHD2 acted as a progesterone receptor associated with lipid hydrolase in the activation of sperm in the reproductive process [ 35 ].…”
Section: Research Progress Related To the Abhd Family Membersmentioning
confidence: 99%
“…3A). Affinity purified His-tagged ABHD2 has esterase activity against p-nitrophenyl conjugated substrates (acetate, butyrate and palmitate) and triacylglycerol lipase activity in vitro although little is known about the substrates hydrolyzed by ABHD2 in vivo [45]. ABHD2 plays a specialized role in sperm flagella where it hydrolyzes 2-arachidonoylglycerol, a negative regulator of sperm-specific calcium channel CatSper, leading to calcium mobilization and sperm activation [46].…”
Section: Discussionmentioning
confidence: 99%